PENGARUH KOMPENSASI FINANSIAL TERHADAP TURNOVER INTENTION DENGAN AFFECTIVE ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL MEDIASI PADA KARYAWAN AYAM BAKAR PAK â€œDâ€ KOTA SURABAYA - Agustina, Tri Siwi (P3M Politeknik Negeri Banjarmasin, 2019)
Financial compensation has an important impact for the company and employees, which in this case is the employees of the Surabaya branch of Ayam Bakar Pak D. However, the problem is whether Financial Compensation has optimally contributed so that it can support the achievement of company goals. This research focuses on how Financial Compensation is able to improve employeeâ€™s Affective Organizational Commitments so that employeeâ€™s Turnover Intention rates can be lower. The variables used in this study are Direct Financial Compensation, Indirect Financial Compensation, Affective Organizational Commitment, and Turnover Intention. This study uses quantitative approach by using questionnaire and Path Analysis method. Respondents of this study are 94 employees in each outlet of the Surabaya branch of Ayam Bakar Pak D. The results of this study indicate that Direct Financial Compensation and Indirect Financial Compensation will increase if Affective Organizational Commitment also increase and Turnover Intention will decrease if Direct Financial Compensation and Affective Organizational Commitment also increase. However, an increase of Indirect Financial Compensation does not impact the increase/decrease of Turnover Intention. Whereas Affective Organizational Commitment mediates the impact of Direct Financial Compensation on Turnover Intention. However, Affective Organizational Commitment does not mediate the impact of Indirect Financial Compensation on Turnover Intention.